Export and benefits of hedging in emerging economies - Udo Broll; Jack E. Wahl; Christoph Wessel (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
We study the impact of exchange rate risk upon export production within an emerging economy lacking in currency forward markets. However there exists a financial asset whose price is correlated with the relevant foreign currency. We present conditions under which export production is stimulated when the hedging device becomes more effective. In any case the exporting firm benefits from imperfectly hedging exchange rate risk.
Keywords: D80; D81; F14; F31; 330; Emerging markets; transition economy; export; exchange rate risk; price risk; hedging